China’s Foreign Direct Investment (FDI) in Malaysia: impact on Malaysia’s Sustainable Development Goals (SDGs) - Norhidayat Zainal; Andrew Kam Jia Yi (Penerbit Universiti Kebangsaan Malaysia, 2023)
Since its initiation, Malaysia has engaged in many BRI-related infrastructure and connectivity projects. These projects, which are mainly Foreign Direct Investments (FDI) from China, have mixed impacts on the three key dimensions enshrined in the UN Sustainable Development Goals (SDGs) - economy, society, and the environment. As FDI from China continues to be an important source of Malaysian economic growth, its contribution to the country’s SDG goals warrants further attention. The study examines China’s FDI impact on Malaysia’s SDG performance and finds that its presence positively influences index scores and global ranking performance. The impact on human capital is encouraging as moderate knowledge transfers and competition enhance workers’ skills. As for the environment, the impact is both positive and negative - gains from China’s investment in green technology but losses in environmental degradation. While the effect on political security and national security is generally positive, the social impact of China’s FDI cannot be determined due to data limitations. The study concludes that Malaysia should continue to engage with China to harness its positive impact toward achieving its SDGs.